2015
DOI: 10.1177/0300060515586007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of meteorological factors on lower respiratory tract infections in children

Abstract: ObjectiveTo evaluate retrospectively the relationship between meteorological factors in Shenmu County, Yulin City, Shaanxi Province, China and the incidence of lower respiratory tract infections in children.MethodsMeteorological data (air temperature, atmospheric pressure, rainfall, hours of sunlight, wind speed and relative humidity) for Shenmu County and medical data from hospitalized patients aged ≤16 years were collected between January 2009 and December 2012. The association between meteorological factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 23 publications
1
28
0
4
Order By: Relevance
“…In temperate climates, RSV detection rates were positively associated with relative humidity . However, some studies undertaken in tropical and subtropical areas have found a positive association with relative humidity, while others have found a negative association . Based on the LASSO model, we found that the RSV detection rate was higher when average relative humidity was low.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…In temperate climates, RSV detection rates were positively associated with relative humidity . However, some studies undertaken in tropical and subtropical areas have found a positive association with relative humidity, while others have found a negative association . Based on the LASSO model, we found that the RSV detection rate was higher when average relative humidity was low.…”
Section: Discussionmentioning
confidence: 47%
“…16,18,21 However, some studies undertaken in tropical and subtropical areas have found a positive association with relative humidity, 12,22,23 while others have found a negative association. 11,20,24 Based on the LASSO model, we found that the RSV detection rate was higher when average relative humidity was low. The incidence of LRTIs has also been shown to be associated with rainfall.…”
Section: Discussionmentioning
confidence: 94%
“…The increased interest of researchers in biometeorological conditions for RTI occurrences includes not only outdoor air temperatures (maximum, minimum, mean), but also wind speed, air humidity, and other meteorological parameters (Liu et al 2016). Biometeorology employs various methods and indices as well as mathematical models to determine relationships between meteorological parameters and human health (Epstein and Moran 2006;Lowe et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory viral infection has been hypothesized to be one of the important causes for febrile seizures and weather conditions are a significant driver of respiratory infections 6) . Air temperature and relative humidity were major influencing meteorological factors for hospital admissions in children due to lower respira tory tract infections 5) . A previous study in Buenos Aires found an increase in lower respiratory infections in children under 5 years old during wintertime 7) .…”
Section: Discussionmentioning
confidence: 99%
“…There were studies that described correlation between meteorological factors and viral infections. One study concluded that air temperature and relative humidity were major influencing meteorological factors for respiratory tract infections 5) . Since respiratory viral in fections are one of the triggering factors of FS, there would be an association between weather and incidence of FS.…”
Section: Introductionmentioning
confidence: 99%